Educational Materials from the Perspective of the Prophet's Hadith - Najwa Nur Fatimah; Rusyaid; Munira Wamu; Faris Ahzamy (Konsultan Jurnal Ilmiah Indonesia, 2025)
Islamic education is a comprehensive system that emphasizes the balance between intellectual development, moral cultivation, and spiritual formation. This study explores the educational values (tarbawi) contained in the Prophet Muhammad’s hadith, particularly the narration of Ibn Abbas, as a fundamental guide for shaping character and ethical behavior in learners. Using a qualitative approach through library research, this study analyzes relevant literature on Islamic education, authentic hadith texts, and scholarly interpretations related to educational principles within Islamic teachings. The findings indicate that the hadith teaches essential concepts such as maintaining a strong relationship with Allah, practicing reliance (tawakkul), and understanding divine decree as core foundations of spiritual education. These values remain highly relevant in modern educational contexts, where intellectual achievements often overshadow moral and spiritual dimensions. The integration of tarbawi principles into contemporary education can foster individuals who are not only intellectually capable but also morally grounded, spiritually conscious, and equipped with noble character. This study highlights the importance of embedding Islamic values in educational processes to develop holistic and balanced human beings.